Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1785/0120030139
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Shear-Wave Splitting in the Aftershock Zone of the 1999 Chi-Chi, Taiwan, Earthquake: Shallow Crustal Anisotropy and Lack of Precursory Variations

Abstract: We analyze shear-wave splitting (SWS) in a high-quality waveform data set recorded at surface and downhole (0.2 km) seismometers in a region around the 20 September 1999 M w 7.6 Chi-Chi, Taiwan, earthquake sequence. The data set was generated by events in a 5-year period before, during, and after the mainshock. The purpose is to investigate the depth extent of the crustal anisotropy and its possible temporal evolution in relation to the occurrence of large earthquakes. Results from downhole records show a stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 38 publications
(36 reference statements)
13
82
1
Order By: Relevance
“…Strong anisotropy may also occur in fault zones where phyllosilicate material is not a major component. Stress-induced anisotropy is often observed in fault zones [e.g., Liu et al, 2004;Cochran and Kroll, 2015]. If the extent of stress-induced anisotropy is significant, then this may also affect seismic imaging of faults in a similar way.…”
Section: 1002/2017gl073726mentioning
confidence: 99%
“…Strong anisotropy may also occur in fault zones where phyllosilicate material is not a major component. Stress-induced anisotropy is often observed in fault zones [e.g., Liu et al, 2004;Cochran and Kroll, 2015]. If the extent of stress-induced anisotropy is significant, then this may also affect seismic imaging of faults in a similar way.…”
Section: 1002/2017gl073726mentioning
confidence: 99%
“…However, Liu et al [2004] demonstrated that spatial variations in seismic sources can be misinterpreted as temporal changes in anisotropy as different ray paths sample different regions of the anisotropic medium. Even though SWS analysis can be used as an indicator of stress and of fluid saturation in the crust, surprisingly few studies have been conducted on shear wave splitting around volcanoes.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the phenomenon of principal stress permutations of (r 1 , r 2 ) and (r 2 , r 3 ) is commonly observed in nature, and it may be caused by strong inhomogeniety and/or anisotropy in the upper crust (HU and ANGELIER, 2004), especially for the highly fractured area. Research indicated that strong anisotropy exists in the upper crust beneath the Chia-Nan area (LIU et al, 2004;CHEN and YEN, 1998). Nevertheless, the results strongly suggest that mixed modes of reverse/strike-slip focal mechanism can exist in a compressional region, which is similar to the study of HU and ANGELIER (2004), and also can be observed in the Costal Range of eastern Taiwan (BARRIER and ANGELIER, 1986).…”
Section: Disscussion and Conclusionmentioning
confidence: 57%